DIVERSIFIKASI OLAHAN PANGAN BERBASIS IKAN UNTUK MENDUKUNG DESA PANCASAN KECAMATAN AJIBARANG SEBAGAI DESA EDUWISATA - Hastuti, Dewi Wisudyanti Budi; Hidayati, Nuning Vita; Riviani, Riviani; Pujihastuti, Etin (Jurnal Abdi Insani, 2024)
Pancasan Village is a village with the theme of Circular Economy Based Edutourism. Pancasan Village is a village located in Ajibarang District, Banyumas Regency, Central Java Province. There are two groups of Fish Farmers (Pokdakan) "Mina Sehat" and "Mina Depok" in Pancasan Village, Ajibarang District, Banyumas Regency which are managed by BUMDes. This Pokdakan has succeeded in completing the knowledge and skills in cultivating fish. In its development, the hope is to enrich knowledge and skills to process fish farming harvests with various product diversification where the results can support the development of the edutourism village program. The aim of this activity is to provide the transfer of knowledge and skills related to the diversification of cultivated fish products provided by competent resource persons.  This activity was carried out at the Pancasan Village Hall on September 8 2024. The superior products that were practiced and transferred were making fish nuggets, fish sushi, fish samosas, fish dim sum and fish dragon feet. This PKM Implementation of Science and Technology activity is able to provide enlightenment and new knowledge for Pokdakan members.